2013
DOI: 10.3171/2013.5.focus13150
|View full text |Cite
|
Sign up to set email alerts
|

Neuronavigation in minimally invasive spine surgery

Abstract: Object Parallel advancements in image guidance technology and minimal access techniques continue to push the frontiers of minimally invasive spine surgery (MISS). While traditional intraoperative imaging remains widely used, newer platforms, such as 3D-fluoroscopy, cone-beam CT, and intraoperative CT/MRI, have enabled safer, more accurate instrumentation placement with less radiation exposure to the surgeon. The goal of this work is to provide a review of the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 49 publications
0
41
0
5
Order By: Relevance
“…The techniques generally use CT imaging with natural fiducial markers that are exposed in the anatomic space. [33][34][35] These techniques are currently under investigation in the veterinary field, and preliminary pilot data have quantitatively shown the ability to place bicorticate implants in ideal bone purchase corridors without spinal column compromise. 36 Transphenoidal hypophysectomy (TSH) is frequently described in the human and veterinary literature but one of the primary limitations of this technique is the lack of consistent external anatomic landmarks that can indicate the safe surgical corridor to the hypophyseal sella.…”
Section: Other Uses For Neuronavigationmentioning
confidence: 97%
“…The techniques generally use CT imaging with natural fiducial markers that are exposed in the anatomic space. [33][34][35] These techniques are currently under investigation in the veterinary field, and preliminary pilot data have quantitatively shown the ability to place bicorticate implants in ideal bone purchase corridors without spinal column compromise. 36 Transphenoidal hypophysectomy (TSH) is frequently described in the human and veterinary literature but one of the primary limitations of this technique is the lack of consistent external anatomic landmarks that can indicate the safe surgical corridor to the hypophyseal sella.…”
Section: Other Uses For Neuronavigationmentioning
confidence: 97%
“…How to master this technique quickly, accurately and is a thorny problem facing in the clinical physician training. We found that computer-assisted navigation technology can significantly shorten the operation period, reduce the amount of blood loss and reduce the error during implantation of screws [5][6][7][8] . It is suggested that intraoperative navigation can significantly shorten the learning curve, reduce the time of screw implantation, reduce the amount of bleeding, improve the accuracy of pedicle screw implantation and avoid the risk of culture.…”
Section: Discussionmentioning
confidence: 99%
“…However, the more minimally invasive the procedure becomes, the more reduced the overview provided. Thus, neuronavigation is increasingly used intraoperatively for the localisation of anatomical structures throughout cranial and spinal neurosurgery [32,33]. When he popularised transsphenoidal surgery, Hardy [34] introduced an image intensifier together with the operating microscope.…”
Section: Neuronavigationmentioning
confidence: 99%